Analysis of the Clinical Case of Long-term Monitoring of a Patient with Comorbid Depression: Special Considerations of Psychopharmacotherapy - V. V. Arkhipov; E. K. Abakumova; Ya. S. Dmitrieva; N. I. Zykova; Yu. R. Bolsunovskaya (Безопасность и риск фармакотерапии, 2020)
Depression associated with somatic diseases ranks high among other depressive disorders and has a number of specifi c clinical features as compared to classic depression.The aim of the study was to analyse specifi c features of comorbid depression clinical course, its diagnosis, and methodology for the selection of psychopharmacotherapy—using a clinical case as an example.Results: the authors carried out a detailed retrospective clinical analysis of medical records of long-term (over three years) dynamic monitoring of a patient with comorbid vascular depression. They explored the tactics of selecting pharmacotherapy for anxiety-depressive disorder given the underlying chronic cerebral ischemia, atherosclerosis of brachiocephalic arteries, аrterial hypertension, and atherosclerotic cardiosclerosis. The primary focus was on specifi c aspects of vascular depression pharmacotherapy that were governed by a diverse clinical picture of comorbid personality disorders, dynamic transformation of somatic, neurological, and psychic symptoms and syndromes in a patient. The paper highlights the need for alignment of scientifi c and methodological approaches to assessment of potential risks associated with the use of psychotropic medicines.Conclusions: the choice of rational psychopharmacotherapy for vascular depression should be governed by the data on the drug effi cacy for the prevailing clinical symptoms, by the age and gender characteristics of the patient, by compensation status of organs and systems, as well as by genetic, personal, and social characteristics that aff ect the disease progression. The use of a comprehensive multidisciplinary approach to the diagnosis and treatment of comorbid personality disorders, as well as implementation of personalised medicine methodology in clinical practice in order to assess the patient’s condition as infl uenced by changes in his/her somatic, neurological, psychic status and the results of psychological testing, will increase the effi cacy and safety of treatment.